Bacteria- their relation to disease - McCullough, William Andrews (My University, 1898)
Introduction: The human mind in its earnest search for the existing realities of the world is constantly before our eyes, those things which nature has seemingly obscured from our view for centuries. In his process of knowledge gathering, we are continually astonished to find that apparently obscure truth were only relatively so; that they are often in plain view, but we have failed to appreciate their presence. We can hardly realize that the true theory regarding the shape of the earth and its relations to other worlds about us, has only been established a few centuries. We can hardly realize that man lived up to the present century without knowing how to utilize the elements of steam, electricity and the gigantic mechanical appliances which are now used. When we look at our high state of development along educational and social lives, we can hardly realize how vastly greater they are than were those of half a century ago.
Citation: McCullough, William Andrews. Bacteria- their relation to disease. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Human Mind; Knowledge; Bacteria; Disease; Theses; Manuscripts (documents)